The singing thing : a case of congregational song - Bell, John L. (Chicago : GIA Publications, Inc., 2000)
An expert on congregational song writes for those who want to encourage others to sing or sing better.
Keywords: Singing -- Religious aspects -- Christianity; Public worship; Hymns; Psalmody